2021
DOI: 10.1155/2021/3987835
|View full text |Cite
|
Sign up to set email alerts
|

Generative Adversarial Network for Damage Identification in Civil Structures

Abstract: In recent years, many efforts have been made to develop efficient deep-learning-based structural health monitoring (SHM) methods. Most of the proposed methods employ supervised algorithms that require data from different damaged states of a structure in order to monitor its health conditions. As such data are not usually available for real civil structures, using supervised algorithms for the health monitoring of these structures might be impracticable. This paper presents a novel two-stage technique based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…In the civil SHM literature, there are also others [ (Wang et al, 2019;Rastin et al, 2021;Yuan et al, 2021;Yang et al, 2022;Huang et al, 2020;Sathya et al, 2020;Sun et al, 2022;Dunphy et al, 2022)] (a total of 10 studies) who are observed that do not fit a category and address different problems. It is observed that the subject of "damage detection after increased resolution" has one study (Sathya et al, 2020) in the literature where the researchers use SRGAN to increase the resolution of the images to improve the performance of the damage classifier.…”
Section: Frontiers In Built Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the civil SHM literature, there are also others [ (Wang et al, 2019;Rastin et al, 2021;Yuan et al, 2021;Yang et al, 2022;Huang et al, 2020;Sathya et al, 2020;Sun et al, 2022;Dunphy et al, 2022)] (a total of 10 studies) who are observed that do not fit a category and address different problems. It is observed that the subject of "damage detection after increased resolution" has one study (Sathya et al, 2020) in the literature where the researchers use SRGAN to increase the resolution of the images to improve the performance of the damage classifier.…”
Section: Frontiers In Built Environmentmentioning
confidence: 99%
“…There is one study on the topic of "track irregularity estimation" on acceleration data (Yuan et al, 2021), one study on the topic of "damage identification" via acceleration data (Rastin et al, 2021), and three studies on the topic of "Annotation reduction via transfer learning" [ (Huang et al, 2020); Dunphy et al, 2022)] which aim to reduce the need of annotating data through transfer-learning are other instances of GAN applications in civil SHM.…”
Section: Frontiers In Built Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al [3] used a BP neural network combined with a modulated broadband mode decomposition (MBMD) method to monitor crane-bearing parts and concluded that the BP neural network has good performance in feature extraction and fault recognition. Rastin et al [4] presented a novel two-stage technique based on generative adversarial networks (GANs) for unsupervised structural health monitoring and damage identifcation. Existing methods to detect structural damage based on the change in structural natural frequency show certain reliability in predicting the location and degree of multiple damage [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Vibration data from IASC-ASCE benchmark structure and TCRF bridge were utilized to evaluate the proposed methodology. Rastin et al [26] used CNNs as generators and discriminator parts of generative adversarial networks to identify damages in civil structures using only healthy state data to train the networks.…”
Section: Introductionmentioning
confidence: 99%